POLA INTERAKSI GURU PENDIDIKAN AGAMA ISLAM DAN PESERTA DIDIK DALAM MEMBENTUK PRIBADI AKHLAQUL KARIMAH DI SMPIT AS SALAM MALANG - Taufiqul Hakim; Imam Safi’i; Moh. Eko Nasrullah (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
In shaping the personality of morality in students, interaction between Islamic religious education teachers and students is needed so that teachers can know student behavior and make it easier for teachers to form morality in students. With this, Islamic religious education teachers carry out several patterns of interaction such as providing motivation and habituation to students, by reading the Qur'an just before the lesson begins, training and providing understanding to students about the importance of a religion, directing students to behave. good in speaking words and attitudes), Familiarize students to follow religious activities at school, By being a good role model.